2017
DOI: 10.1038/srep43601
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of SKN-1 modulates the lifespan and oxidative stress resistance in Caenorhabditis elegans

Abstract: In C. elegans, the transcription factor skinhead-1 (SKN-1), the ortholog of human NF-E2-related factor 2 (Nrf-2), plays important roles in oxidative stress defense and aging processes. It has been documented that the activity of SKN-1 is regulated by its phosphorylation modification. However, whether other posttranslational modifications of SKN-1 affect its function remains unclear to date. Here we report, for the first time, that SKN-1 is O-GlcNAcylated at Ser470 and Thr493 by O-GlcNActransferase OGT-1. By ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Therefore, we speculate that TCF11 somehow has attained an opposite OGT mediated regulatory mechanism as it began to be expressed later in phylogeny. In this regard, it is interesting that SKN1, an Nrf1 ortholog present in C. elegans, was recently shown to be positively regulated by an OGT interaction similar to that with Nrf1a shown in our investigation [72]. As of now however, there are no studies elucidating the functional difference between TCF11 and Nrf1a.…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, we speculate that TCF11 somehow has attained an opposite OGT mediated regulatory mechanism as it began to be expressed later in phylogeny. In this regard, it is interesting that SKN1, an Nrf1 ortholog present in C. elegans, was recently shown to be positively regulated by an OGT interaction similar to that with Nrf1a shown in our investigation [72]. As of now however, there are no studies elucidating the functional difference between TCF11 and Nrf1a.…”
Section: Discussionmentioning
confidence: 62%
“…C. elegans is the primary genetic model system for studies of ogt-1 because it is the only organism in which loss of ogt-1 is viable (25,26). This has allowed many previous studies to parse the roles of ogt-1 in lifespan, metabolism, innate immunity, behavior, neuron function, stress responses, cell fate, and autophagy (18,22,25,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Importantly, most of these studies utilized global ogt-1 knockdown, which eliminates both O-GlcNAcylation-dependent and -independent functions of ogt-1.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data has shown that it plays both a transcriptional and posttranscriptional role in stress response gene expression. For example, OGT-1 O-GlcNAcylates the oxidative stress responsive transcription factor SKN-1 to facilitate upregulation of antioxidant gene transcription (32). On the other hand, OGT regulates UPR ER and HSR gene expression post-transcriptionally by O-GlcNAcylating translation initiation factors to selectively facilitate translation of stress induced mRNAs (43,44).…”
Section: Knockout Of Ogt In Mammalian Cells Leads To a Rapid Loss In mentioning
confidence: 99%
“…Interestingly, recent studies have identified cross‐talk between O‐GlcNAcylation and the NRF2 pathway in different species and experimental models. For example, SKN‐1, the NRF ortholog in Caenorhabditis elegans , is O‐GlcNAcylated in response to oxidative stress (Li et al , ). Although we did not detect evidence of NRF2 O‐GlcNAcylation under homeostasis conditions (Fig A), human NRF proteins may be glycosylated in response to oxidative stress or other triggers.…”
Section: Discussionmentioning
confidence: 99%